PENGARUH VARIASI JUMLAH FASTENER TERHADAP KEKUATAN STRUKTUR REPAIR LONGITUDINAL FLOOR BEAM PESAWAT B737-300 - Santoso, Djarot Wahju (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
Longitudinal floor beam structure is a rod that serves to support the weight of the passenger seat, the passenger load and luggage on airplanes. Bending load received by the structure continuously during flight operations cause damage (cracks). The presence of cracks in the structure of the repair needs to be done to ensure the safety of the aircraft during operation. Structure Repair Manual (SRM) is a guide issued by the manufacturer of the aircraft maintenance company to do the repair. In SRM was not stated clearly that the repair is safe. To determine the level of safety o f longitudinal floor beam structure repair Boeing 737-300 fractured analysis is needed also to determine the effect of the number of fasteners to the strength of the modified structure. Modeling and analysis of longitudinal structural floor beam using CATIA V5R16 software. Imposition o f the structure using a bending load due to the load compartment main cabin. Four models are made in accordance with the repair of such structures to handle SRM model fractured. Modifications done by reducing fastener types BACB30FN6 6 to 5 and 4 fastener on the upper area of the beam. Static analysis performed on models with CATIA V5R16 to determine the safety o f the structure is based os margin of safety.The results of analysis that the longitudinal floor beam structural repair the fractured secure against bending loads. The use of a modified structure repair by reducing the number of fastener would increase the critical stress that occurs, but the structure is still safe to load.